2018
DOI: 10.1016/j.ijantimicag.2017.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Co-infection with influenza-associated acute respiratory distress syndrome requiring extracorporeal membrane oxygenation

Abstract: The co-infection frequency and impact among influenza-associated acute respiratory distress syndrome (ARDS) patients requiring extracorporeal membrane oxygenation (ECMO) are not known. This retrospective observational analysis concerned data prospectively collected from patients admitted to our medical intensive care unit (ICU) who received ECMO support for influenza-associated ARDS between 2009-2016. Co-infection was defined as occurring within 48 h following ICU admission. Among the 77 ARDS patients requirin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 30 publications
2
30
0
Order By: Relevance
“…Influenza plays a dominant role in co-infection, which was so severe that needed effective means to decrease death. The Influenza patients diagnosed with severity score CURB 65 and detection method mPCR can be admitted to ICU sooner and start treatment like ECMO and Tamiflu sooner with increased survival (5,6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Influenza plays a dominant role in co-infection, which was so severe that needed effective means to decrease death. The Influenza patients diagnosed with severity score CURB 65 and detection method mPCR can be admitted to ICU sooner and start treatment like ECMO and Tamiflu sooner with increased survival (5,6).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, severe hypoxemic acute respiratory failure and acute respiratory distress syndrome (ARDS) were strongly associated with influenza A (H1N1) in 2009 (3,4). The influenza outbreak was so severe that extracorporeal membrane oxygenation (ECMO) was used to decrease death (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Current data still lacks proof that the clinical presentation with viral-bacterial co-infections directly leads to worse outcomes, but a growing body of evidence suggests that influenza-bacterial co-infections are associated with higher morbidity and higher mortality [65,[73][74][75][76]. In fact, a recent study showed that the presence of co-infection in adults with influenza-associated acute respiratory syndrome requiring extra-corporeal membrane oxygenation was significantly associated with a fourfold increase in mortality [77], and another study in children with Staphylococcus aureus co-infection with influenza-related critical illness also showed a ninefold significant increase in mortality [78].…”
Section: Role Of Viral-bacterial Co-infections and Their Effect On Oumentioning
confidence: 99%
“…Data from several large observational studies suggest, overall, that there is a probable benefit to be derived from the use of ECLS in H1N1-associated severe ARDS refractory to conventional therapy [13][14][15]. Whereas no specific infectious etiology has been identified as a contraindication to the use of ECLS, co-infections in the context of influenzaassociated ARDS, including infections with S. aureus, multidrug-resistant Gram-negative bacteria and Aspergillus, may correlate with lower survival compared with influenza alone [16][17][18][19]. Likewise, concomitant nonpulmonary infections at the time of initiation of ECLS for ARDS may predict worse outcomes and this factor has been incorporated into a validated prognostic scoring system [20].…”
Section: Infections Prior To the Initiation Of Eclsmentioning
confidence: 99%